REBRANDING USAHA BENGKEL OTOMOTIF MELALUI DESAIN KONTEN INSTAGRAM DAN MEDIA PROMOSI - Halimi, Halimi; Prakoso, Satriya Agung; Rochmaniah, Ainur; Febriana, Poppy (LP2M Universitas Bina Bangsa, 2025)
The workshop business is a competition with high competitiveness with many competitors engaged in vehicle repair services. Fierce competition between automotive workshops encourages more effective, innovative and solution-oriented business branding. The